2018
DOI: 10.1093/gerona/gly235
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Lipid Content Has Sex-Specific Associations With Whole-Muscle, Cellular, and Molecular Contractile Function in Older Adults

Abstract: Increased adiposity is associated with reduced skeletal muscle function in older adults, but the mechanisms underlying this relationship remain unclear. To explore whether skeletal muscle properties track with adiposity, whole-muscle, cellular, and molecular function were examined in relation to adiposity measured at various anatomical levels in healthy older (60–80 years) men and women. Although women had greater absolute and relative body and thigh fat than men, quadriceps muscle attenuation, an index of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Besides metabolic associations, excess adiposity also affects functional capacity. Lower muscle density, reflecting increased adipose tissue infiltration into the muscle compartment, is associated with whole‐body adiposity (Goodpaster et al, 2000 ) and can lead to decreased muscle power and postural balance (Straight et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides metabolic associations, excess adiposity also affects functional capacity. Lower muscle density, reflecting increased adipose tissue infiltration into the muscle compartment, is associated with whole‐body adiposity (Goodpaster et al, 2000 ) and can lead to decreased muscle power and postural balance (Straight et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Choi et al found that the older adults with obesity exhibited impairments in unloaded shortening velocity (V 0 ) in MHC I fibres (slow), and impaired maximal force output in MHC I fibres and MHC IIa fibres (fast) relative to the older adults who did not have obesity. Straight et al (2019) found that adiposity was negatively correlated with single fibre force per CSA in MHC I and IIa fibres of older women, but not older men. We are not aware of any study which has examined the effects of obesity on contractility of single muscle fibres from young humans or from animals.…”
Section: R a F Tmentioning
confidence: 87%
“…Intramuscular fat elicits numerous skeletal muscle adaptations that may ultimately contribute to decline in whole-muscle function and, thereby, gait and mobility. For example, intramyocellular fat content in older adults with obesity is associated with larger single fiber cross-sectional area and slower peak shortening velocity and specific power [ 30 , 31 ]. These impairments at the myofibril level subsequently contribute to reduced peak force from individual muscle fibers in persons with compared to those without obesity [ 30 ].…”
Section: Biomechanics and Gait Performancementioning
confidence: 99%